Climate change and the 2030 corporate agenda for sustainable development - Leonard, Liam; Gonzalez-Perez, Maria Alejandra (Advances in sustainability and environmental justice ;, 2016)
This volume explores the meaning of the Paris Climate Agreement 2015 for business; it analyses its challenges and implications, and establishes required actions by the private sector in order to reduce global warming and mitigating climate change effects. We bring together evidence-based, conceptual and theoretical contributions from a diverse set of geographical locations, and disciplinary backgrounds on the meanings, implications, opportunities and challenges for business around the planet in relation to climate change.